Occurrence of Multidrug-Resistant Candidiasis Among Pregnant Women at a Peri-Urban Hospital, Uganda - Lucas Ampaire; Deogratious Mukasa; Marvin Bikamatte; Winston Katatanzi; Emmanuel Mukula; Agnes P. Akello; Aggrey Byaruhanga; Enoch Muwanguzi; Moses Ocan; Benson Okongo; Jazira Tumusiime; Charles Nkubi Bagenda (Cureus, 2025)
Introduction: Vulvovaginal candidiasis (VVC) is one of the most common non-bacterial infections in women worldwide. The common causative yeasts are Candida albicans and Candida krusei. Limited studies on antifungal resistance have been conducted in low-resource settings like Uganda. In this study, we aimed to establish the prevalence and drug susceptibility patterns of VVC among pregnant women at a peri-urban private not-for-profit referral hospital in Uganda. Methods: A total of 352 vaginal discharge swabs were collected from consenting pregnant women attending the antenatal clinic of Kisubi Hospital, Uganda. Microscopy and culture on Sabouraud dextrose agar were used for primary screening. Candida species identification and differentiation were achieved using the germ tube tests and Candida Chromogenic Agar (Oxoid Ltd, Hampshire, United Kingdom). Antifungal susceptibility testing was performed using the standard Kirby-Bauer diffusion method as previously described. We included voriconazole (1 μg), fluconazole (100 μg), itraconazole (1 μg), nystatin (100 μg), caspofungin (5 μg), and interpreted as per the guidelines of Clinical Laboratory Standard Institute 2022. We used SPSS Statistics for Windows, version 15 (SPSS Inc., Chicago, Illinois, United States) for descriptive analysis of the data. Results: Candida species were isolated in 93 (26.4%) pregnant women studied. These included C. albicans (n=51, 43.2%), C. krusei (n=46, 39.0%), Candida tropicalis (n=9, 7.6%), and unidentified Candida species (n=12, 10.2%). All Candida species showed resistance to at least one class of drug, with a total resistance of 86.9% and a multidrug resistance of 56.3%. C. albicans and C. krusei exhibited the most resistance up to 100% to azoles and caspofungin. All species exhibited the least resistance to nystatin at 76.3%. Conclusion: C. albicans and C. krusei remain significant causes of candidiasis among pregnant women in our setting. The observed multidrug resistance in C. albicans poses a great threat to the management of candidiasis.
Keywords: antifungal resistance; candida albicans; candida krusei; candida tropicalis; pregnancy; vulvovaginal candidiasis